Analysis on the efficacy and safety of chemotherapy combined with or without bevacizumab after CRS+HIPEC in patients with malignant peritoneal mesothelioma: a single-center retrospective study - Yang, Zhi-Ran; Liang, Xin-Li; Li, Xin-Bao; Zhang, Xin-Jing; Wu, He-Liang; Su, Yan-Dong; Li, Yan; An, Song-Lin (Frontiers in Oncology, 2026)
ObjectiveTo investigate the efficacy and safety of pemetrexed/platinum-based chemotherapy combined with or without bevacizumab after cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) in the treatment of patients with malignant peritoneal mesothelioma (MPM).MethodsA retrospective non-randomized study was performed on 205 MPM patients treated with CRS+HIPEC at our institution. A total of 97 eligible patients were analyzed: 58 patients who received postoperative chemotherapy combined with bevacizumab (C&B) and 39 patients who received chemotherapy alone (C) were divided into a study group and a control group, respectively. The patients were also divided into the bevacizumab-exposed subgroup and the bevacizumab-unexposed subgroup based on whether they had a history of bevacizumab infusion. Clinicopathological data and follow-up information were statistically analyzed. Independent prognostic factors were identified via survival analysis, and the safety of combination therapy was assessed via adverse event analysis.ResultsAs of the follow-up cutoff date of July 1, 2025, in both the subgroups with and without a history of bevacizumab infusion, there was no statistically significant difference between the control and study groups in baseline pathological characteristic parameters (p > 0.05). Survival analysis revealed that in the subgroup of patients with a history of bevacizumab infusion, the difference in median overall survival (mOS) between the control and study groups was statistically significant (31.9 months vs. NR; p = 0.031), and the difference in median disease-free survival (mDFS) between the control and study groups was statistically significant (12.5 months vs. NR; p = 0.001); in the subgroup of patients without a history of bevacizumab infusion, the difference in mOS between the control and study groups was also statistically significant (20.5 months vs. NR; p = 0.001), and the difference in mDFS between the control and study groups was statistically significant (13.2 vs. 36.2 months; p = 0.001). The Cox regression model found that postoperative C&B was an independent prognostic factor (p = 0.009, HR = 0.081, 95% CI: 0.012–0.526) in the subgroup with a history of bevacizumab infusion, and the Ki-67 index (p = 0.043, HR = 2.563, 95% CI: 1.029–6.386) and postoperative C&B were independent prognostic factors (p = 0.01, HR = 0.086, 95% CI: 0.032–0.232) in the subgroup with no bevacizumab treatment history. A total of 101 cases of grade 1~2 adverse events in the study group were revealed via adverse event analysis, with common events including nausea/vomiting, fatigue, leukopenia/neutropenia, thrombocytopenia, anemia, abnormal liver function, hypertension, and proteinuria. There were four cases with grade 3 adverse events, mainly leukopenia/neutropenia, hypertension, and proteinuria. In the control group, there were 84 cases of grade 1~2 adverse events, and three cases of grade 3 adverse events were observed.ConclusionOur exploratory findings suggest that bevacizumab combined with pemetrexed/platinum-based chemotherapy may be a therapeutic option for MPM patients after CRS+HIPEC; however, a prospective, randomized controlled clinical study is needed to validate our findings.